2015
DOI: 10.1007/s12591-015-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamics of a Tumor–Immune System with Chemotherapy and Immunotherapy and Quadratic Optimal Control

Abstract: In this paper, we consider a tumor growth model with the effect of tumor-immune interactions and chemotherapeutic as well as immunotherapeutic drugs. In our model there are four compartments, namely tumor cells, immune cells, chemotherapeutic drug concentration and immunotherapeutic drug concentration. The dynamical behaviour of our system by analyzing the existence and stability of our system at various equilibria is discussed elaborately. We set up an optimal control problem relative to the model so as to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The current trend of use of chemoimmunotherapy in cancer research in general [26] has boosted several studies on mathematical oncology (e.g. [27,28,29,30]). In a practical sense, chemoimmunotherapy is becoming more and more a need for successful CLL treatments [31], but only a few studies are aimed at modeling (e.g.…”
Section: R a F Tmentioning
confidence: 99%
“…The current trend of use of chemoimmunotherapy in cancer research in general [26] has boosted several studies on mathematical oncology (e.g. [27,28,29,30]). In a practical sense, chemoimmunotherapy is becoming more and more a need for successful CLL treatments [31], but only a few studies are aimed at modeling (e.g.…”
Section: R a F Tmentioning
confidence: 99%
“…Valuable and comprehensive reviews can be found in [32][33][34][35]. Most of these models are in the form of a system of coupled nonlinear ordinary differential equations (see, for example, references [12,[36][37][38][39]). Along this line, de Pillis and colleagues developed a useful model for the interaction between the tumor and immune system [13,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling is the most important part of these researches. With the help of mathematical models, researchers obtain very crucial information about the spread of diseases and measures to be taken [1][2][3].…”
Section: Introductionmentioning
confidence: 99%